MODERATING EFFECT OF PURPOSE OF TRAVEL ON PASSENGER SATISFACTION BEFORE AND DURING PANDEMIC COVID-19 - Astri Desiana; Ardhianiswari Diah Ekawati (Media Bina Ilmiah, 2023)
Since COVID-19 was declared as a pandemic, there have been major changes at the airports which can affect passenger satisfaction on service quality. This study examined key drivers of passenger satisfaction before and during the COVID-19 pandemic based on the airport service quality framework by Airport Council International (ACI) and the moderating effect of passenger purpose of travel on relationship between airport service quality and passenger satisfaction. The population was domestic flight passengers who departed through Adi Soemarmo International Airport on the period of May 2018 – December 2021. The data were analyzed using PLS-SEM Multi Group Analysis. The result showed that airport environment and airport facilities were the key drivers of passenger’s satisfaction for both of group, while security is key driver only for passenger during pandemic and find your way for passenger before pandemic only. This study also show that purpose of travel is moderating the effect on passenger satisfaction of airport environment and facilities on passenger before pandemic and security on passenger during pandemic.